Analisis Prediktif Dan Optimasi Pengaruh Ketinggian Pahat Insert Carbide Pada Proses Turning Terhadap Kekasaran Permukaan Pada Material Bantalan Luncur (Bronze) - candra prilyanto (Media Aplikom, 2019)
World Industries and Small and Medium Enterprises (SMEs) are being encouraged by the government to be able to competitiveness. It means that innovation, efficiency, and productivity are compulsory to be achieved at any time. On the other hand, buying high-tech machines such as CNC Lathe machine requires no small cost. Material Bronze is one type of material that is often used as spare parts sliding bearings (Bush). This study innovates by making a breakthrough. The carbide inserts CCMT09T304 type used on CNC lathes will be applied for use on conventional lathes in making sliding bearings. The carbide insert with Speed ​​Cutting technology is the ability of a greater meaning will enable Bronze material slashed /processed at a higher rotation speed and a larger burial will produce products with a better time. This research is to obtain machining parameters such as spindle speed rotation (Rpm), feedings (mm / rotation) and tools height position above the center (mm). The method used is the experimental method. Preparation of specimens was performed with the Taguchi approach, independent variables were height position tools (mm), spindle speed rotation (Rpm), feedings (mm / rotation), the control variable is the depth of cut 0.5 mm.